Metastasis in differentiated thyroid carcinoma - Azim, MA; Salam, KS; Khan, MK; Khan, JA; Hussain, MA; Kundu, SC; Mostafa, MG (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):497-503 The abstract of this article is available on the PubMed website